1951
DOI: 10.1113/jphysiol.1951.sp004512
|View full text |Cite
|
Sign up to set email alerts
|

The tension and resistance to stretching of human skin and other membranes, with results from a series of normal and oedematous cases

Abstract: Dick (1947) described the structure and arrangement of elastic tissue in normal and in oedematous skin. In this paper the resistance of the skin to stretching is investigated and the part played by elastic tissue in the tension of the skin is discussed. Hass (1939) reviewed the properties ofelastic tissue in general and emphasized, as had the German school at an earlier date (Sternberg, 1925), that changes in staining properties of elastic fibres did not necessarily signify changes in function or structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
1

Year Published

1957
1957
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(16 citation statements)
references
References 3 publications
1
14
0
1
Order By: Relevance
“…Rothman (1953) observed that old people's skin had a poor elasdc meshwork producing low initial tension. Schmitt (1891) referred to the breakdown of elastic tissue with age and these findings were confirmed by Ejiri (1937) and Dick (1947). Wenzel (1949) observed that the contraction of skin was greater in the direction of Ranger's lines than across it.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Rothman (1953) observed that old people's skin had a poor elasdc meshwork producing low initial tension. Schmitt (1891) referred to the breakdown of elastic tissue with age and these findings were confirmed by Ejiri (1937) and Dick (1947). Wenzel (1949) observed that the contraction of skin was greater in the direction of Ranger's lines than across it.…”
Section: Discussionsupporting
confidence: 59%
“…Schade, 1912;Dick, 1949;Carter and Rangy, 1954) have failed to measure any specific property of the material or to relate the find ings to the structure of the tissue. In recent years more interest has been aroused in this field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical properties of skin as influenced by age and by various pharma cological factors have been studied by many authors (Brozek and Kinzey, 1960;Dick, 1951;Fry et al, 1964;Grahame and Holt, 1969;Harkness, 1961;Harkness and Harkness, 1966;Holzmann et al, 1971;Jansen and Rottier, 1958;Kenedi et al, 1964Kenedi et al, , 1966Lanir and Fung, 1974;Mendoza andMilch, 1964/1965;Millington et al, 1971;Wright, 1964, 1966;Rollhäuser, 1950;Ruppelt, 1937;Schade, 1912;Schmidt-La Baume, 1927a, b, 1928, Stütt gen. 1965Vogel, 1969Vogel, , 1971Vogel, , 1972aVogel, , b, c, 1973Vogel, , 1974aVogel etaL, 1970;Weinig and Zink, 1967;Wenzel, 1950).…”
mentioning
confidence: 99%
“…One of the first in vitro studies of the tension and resistance of human skin was carried out by Dick (1951). He stretched pieces of skin over water in a round chamber and measured the excursion of the centre of the circle of skin in response to increases in the water pressure beneath the skin.…”
mentioning
confidence: 99%